The Black Newspaper and the Chosen Nation - Fagan, Benjamin (Book collections on Project MUSE., 2016)
"The Black Newspaper and the Chosen Nation shows how antebellum African-Americans used the newspaper as a means of translating their belief in black "chosenness" into plans and programs for black liberation. During the decades leading up to the Civil War, the idea that God had marked black Americans as his chosen people on earth became a central article of faith in northern black communities, with black newspaper editors articulating it in their journals. Benjamin Fagan examines how the early black press helped shape the relationship between black chosenness and the struggles for black freedom and equality in America, in the process transforming the very notion of a chosen American nation. Exploring how cultures of print helped antebellum black Americans apply their faith to struggles grand and small, The Black Newspaper and the Chosen Nation uses the vast and neglected archive of the early black press to shed new light on many of the central figures and questions of African American studies."--Publisher's description.